Electrochemical deposition of aluminum on W electrode from AlCl3-NaCl melts - 阚洪敏 王兆文 王晓阳 张宁 (Transactions of Nonferrous Metals Society of China, 2010)
Electrochemical deposition of aluminum on W electrode from AlCl3-NaCl melts was studied by cyclic voltammetry and chronopotentiometry. The results show that Al （III） is reduced in two consecutive steps, i.e., 4Al2Cl7-＋3e^-→Al＋7AIC14- and then AlCl4^-＋3e^-→Al＋4Cl^-. The electrochemical reaction of 4Al2Cl7^-＋3e^-→Al＋7AlCl4^- is reversible. Certain nucleation overpotential is required during the deposition of aluminum on W electrode. Chronopotentiometry analysis also shows that Al （Ⅲ） is reduced in two consecutive steps under certain current density, which is in reasonable agreement with cyclic voltammograms. By using constant current deposition, the electrodeposits on Al substrate obtained at between 50 and 100 mA/cm^2 are quite dense and well adherent to the Al substrate. The electrochemical deposition of aluminum on Cu substrate in AlCl3-NaCl melts indicates that the intermetallic compounds are formed. The intermetallic compounds are AlCu and Al2Cu.